Vibrational Assignments and Normal Coordinate Analysis of 2-Fluorenyl Methyl Ketone. - ILANGO, G.; ARIVAZHAGAN, M.; BALACHANDRAN, V.; JOHN XAVIER, R. (Asian Journal of Chemistry, 2010)
The FT-IR and FT-Raman spectra of 2-fluorenyl methyl ketone have been recorded. The observed frequencies were assigned to various modes of vibrations on the basis of normal coordinate calculations, assuming CS point group symmetry. The potential energy distribution associated with normal modes is also reported here. The assignment of fundamental vibrations agrees well with the calculated frequencies.